2013
DOI: 10.1007/s00247-013-2804-0
|View full text |Cite
|
Sign up to set email alerts
|

Routine perinatal and paediatric post-mortem radiography: detection rates and implications for practice

Abstract: Routine post-mortem paediatric radiography in foetuses and neonates is neither diagnostically useful nor cost-effective. A more evidence-based, selective protocol should yield significant cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 14 publications
0
38
1
Order By: Relevance
“…Arthurs et al identified 1027 cases in their institution of which 739 (72%) babygrams and 288 full skeletal surveys (28%) with an overall "abnormality" rate of 12.3% [31]. The abnormality rate was higher for skeletal surveys (18%) than babygrams (10%).…”
Section: Routine or Targeted Pmss?mentioning
confidence: 97%
See 3 more Smart Citations
“…Arthurs et al identified 1027 cases in their institution of which 739 (72%) babygrams and 288 full skeletal surveys (28%) with an overall "abnormality" rate of 12.3% [31]. The abnormality rate was higher for skeletal surveys (18%) than babygrams (10%).…”
Section: Routine or Targeted Pmss?mentioning
confidence: 97%
“…Based on these criteria, two recent studies in the UK and Netherlands have evaluated this issue in the light of modern antenatal US diagnostic techniques and modern day practices [31,32]. Arthurs et al identified 1027 cases in their institution of which 739 (72%) babygrams and 288 full skeletal surveys (28%) with an overall "abnormality" rate of 12.3% [31].…”
Section: Routine or Targeted Pmss?mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the cost of performing an individual radiograph may also be relatively low, when used as a form of routine screening investigation this may not be cost-effective, especially in busy units performing several hundred investigations per year (2).As cross-sectional imaging studies have become a routine part of diagnostic clinical practice, these new imaging modalities are slowly being adopted into post-mortem investigations.…”
Section: Introductionmentioning
confidence: 99%